Retribusi Izin Mendirikan Bangunan dan Permasalahannya Studi pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Ira Rahmayanti; Amida Wahyuni Lubis (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the process of obtaining a Building Permit (IMB) and the administration of a Regional Levies Determination Letter (SKRD) which is often not paid by the applicant, resulting in a levy receivable at the Medan City Investment and One Stop Service Office. This study uses an exploratory qualitative analysis method. Qualitative data was obtained by means of interviews, observations and documentation studies and the validity and reliability of the data were determined by data triangulation, then the data obtained would be analyzed thematically and interpreted to draw conclusions. The results showed that the processing of the IMB issuance experienced a delay in the processing of files by the IMB technical team so that it had implications for the delay in the issuance of the IMB document. Another consequence that occurs is the loss of potential regional income from IMB retribution due to delays. Receivables due to levies occur because the applicant does not pay the IMB SKRD at the bank according to the stipulated time. Keywords: Building Permits, processing of regional levy determination letters, accounts receivable